2016
DOI: 10.5588/ijtld.15.0807
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among patients with pulmonary non-tuberculous mycobacteria disease

Abstract: PNTM remains a serious public health concern, with a consistently elevated mortality rate across multiple populations. Significant risk factors for death include fibrocavitary disease and pulmonary hypertension. Further research is needed to more specifically identify clinical and microbiologic factors that jointly influence disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 30 publications
7
48
1
2
Order By: Relevance
“…In addition, most prior studies comprised patients from NTM clinics, which permitted careful clinical characterization but most likely led to substantial bias in patient selection ( 7 , 8 , 10 ). Although our 5-year mortality estimates (26.6% for NTM-PI and 36.9% for NTM-PD) were of generally similar magnitude to prior studies ( 7 11 ), parsing those studies by cohort type reveals that those comprising single NTM clinics tended to report lower rates of death ( 7 , 8 , 10 ). In the single-clinic study from the United States, which had the lowest 5-year death rate of 18% ( 10 ), the median age at diagnosis was 55 years, compared with 70 years in our study, which probably explains much of the difference in death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most prior studies comprised patients from NTM clinics, which permitted careful clinical characterization but most likely led to substantial bias in patient selection ( 7 , 8 , 10 ). Although our 5-year mortality estimates (26.6% for NTM-PI and 36.9% for NTM-PD) were of generally similar magnitude to prior studies ( 7 11 ), parsing those studies by cohort type reveals that those comprising single NTM clinics tended to report lower rates of death ( 7 , 8 , 10 ). In the single-clinic study from the United States, which had the lowest 5-year death rate of 18% ( 10 ), the median age at diagnosis was 55 years, compared with 70 years in our study, which probably explains much of the difference in death.…”
Section: Discussionmentioning
confidence: 99%
“…At the population level, patients with NTM-PD have been poorly characterized in general, and their survival is not well studied. Studies from individual clinical programs have identified prognostic factors ( 7 10 ), but estimates of survival are undoubtedly affected by referral bias and therefore cannot be generalized to all NTM-PD patients. One population-based study of survival in NTM-PD patients has been reported, but it did not include controls without NTM, so NTM-attributable death could not be determined ( 11 ).…”
mentioning
confidence: 99%
“…Impaired innate immunity due to lung parenchyma damage is believed to be the major predisposing factor for PNTM infection. PNTM disease is a serious cause of morbidity and mortality and has a rising incidence across populations [6, 7]. In cases with no past medical or family history suggestive of immunodeficiency, a deficiency in the production of IFN- γ has previously been noted prompting the adjuvant use of IFN- γ therapy [810].…”
Section: Discussionmentioning
confidence: 99%
“…From a pathophysiologic perspective, this recognition has changed the way that many NTM experts view the development of NTM lung disease. Specifically, because NTM exposure is universal but NTM disease is relatively rare, it is increasingly accepted that patients require not only exposure to NTM but also likely some type of predisposition, such as the structural lung abnormalities most often associated with bronchiectasis or obstructive lung disease 38 . This hypothesis has been dubbed the “two-hit” theory of NTM lung disease acquisition.…”
Section: Pathophysiologymentioning
confidence: 99%